Gamma knife stereotactic radiosurgery yields good long-term outcomes for low-volume uveal melanomas without intraocular complications - (:unkn) unknown (ELSEVIER SCI LTD, 2010)
We present the outcomes of 35 uveal melanoma patients treated with gamma knife stereotactic radiosurgery. All cases were previously untreated. During follow-up, regular MRI examinations were used to detect any changes in tumor size and estimate the local long-term tumor control rate. Treatment-related complications were also recorded. During follow-up, systemic dissemination was observed in two patients, one of whom died of metastases. The most frequent complication was retinal detachment (17.1%). Three patients required enucleation. Cumulative I-year and 3-year local tumor growth control rates were 97% and 83%, respectively. The mean and median times to local tumor progression were 48.0 and 51.7 months, respectively. Gamma knife surgery may be a suitable alternative for the treatment of low-volume uveal tumors without intraocular complications, as the control rate and long-term outcomes compare favorably with those of surgical excision and brachytherapy. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Uveal melanoma; Gamma knife radiosurgery; Local tumor control; Stereotactic radiosurgery; Local disease control; PLAQUE RADIOTHERAPY; TRANSPUPILLARY THERMOTHERAPY; CHOROIDAL MELANOMA; BEAM IRRADIATION; TUMOR-CONTROL; ENUCLEATION; EXPERIENCE; MANAGEMENT